Machado-Joseph Disease, A Case Report of Treatment Based on Phototherapy - Hugo Mendieta Zerón; David Emmanuel González Mendoza; Pamela Lagos Robles; Miriam Deyanira Rodriguez Piña (Caucasian Medical Journal)
Machado-Joseph disease (MJD) is a rare autosomal dominant disease caused by a mutation in exon 10 of the ATXN3 gene resulting from a cytosine-adenine-guanine trinucleotide repeat. A case of a 48-year-old man with MJD is reported. His father, two paternal aunts, and his older sister all died because of this disease, and his younger brother had the same disease. Due to the absence of therapeutic options, phototherapy sessions were offered as an alternative between 425 and 650 nm 1.33 Joules/cm2, 30 cm above the chest. After three months of phototherapy sessions, the following items showed a decrease in their scores: physical functioning, role limitations due to physical health, role limitations due to emotional problems, energy/fatigue, emotional well-being, social functioning, and general health. The only variable that remained unchanged was pain. He discontinued treatment, attributed the deterioration to phototherapy. A year later, as the disease progressed, he decided to resume the same scheme, and the following trends were observed: a) Improvement in role limitations due to physical health, emotional well-being, social functioning, and general health; b) No changes in role limitations due to emotional problems and pain and c) deterioration in energy/fatigue.